DESAIN RODA BESI BERSIRIP TRAKTOR DUA-RODA DENGAN BANTUAN (CAD). - Irwin Syahri Cebro; Wawan Hermawan; Desrial . (PERTETA, 2006)
Abstract Traction performance of a cage wheel for two-wheel tractor depends on its shape dimension, lugs materials and soil condition. In order to get the optimum design of the cage wheel, the relation betwen tractor, implement and soil condition should be considered carefully. The objective of this research was to determine optimum design parameter of cage wheel based on working condition of tractor and to make a computer program for design analysis and for producing engineering drawing of the cage wheels. Soil condition and two-wheel tractor construction were measured and the data was used for getting the optimum design parameters by using optimization method. A computer program was developed and employed for the optimization process and for drawing the design result. As a trial of the program, the optimum design parameters of cage wheel for Yanmar YST-EX tractor working at Sawah Baru rice field were found to be: 80 cm of wheel diameter: 10 lugs: 19.63 cm x 9.68 c, of lug size; and 20o of lug angle. The result revealed that the program could determine the optimum design parameters and could produce the engineering drawing of the cage wheel property. Keyword: cage wheel. Design parameter, engineering drawing, computer program.